The Attractiveness of "the Ecological" in Modern Fashion Experiments: A Discursive Study - Budіak, Victoria; Yermakova, Tetiana; Tokar, Maryna (HUDPROM: The Ukrainian Art and Design Journal, 2024)
The article explores the concept of ecological design and its role in contemporary fashion. "Eco-fashion" is a relatively new term in the industry, referring to clothing made from environmentally friendly materials grown without harmful chemicals or fertilizers. The labels "100% Natural", "Eco-Friendly", "Green" attract consumers who prioritize their health and seek to minimize their impact on the environment. The article argues that the relevance of this topic is driven by several key factors, including environmental protection and conservation, the use of natural materials and dyes, zero-waste production, and the principles of limited consumption and wardrobe minimization. The concept of "vestimentary fashion" is introduced, highlighting its connection to ecological design. The relevance of eco-design in the global fashion industry is examined through the examples of vestimentary fashion. An analysis of the leading designers and brands reveals a growing trend of dedicated "eco-collections." These collections feature garments made from undyed and untreated natural fabrics, with buttons, fasteners, hooks, and other details crafted from sustainable materials such as bone, mother-of-pearl, metal, and wood. The article also highlights "conscious" design methods employed by both international and Ukrainian fashion designers. Furthermore, the distinction between fast and sustainable fashion is explored, outlining the defining characteristics of the latter and the primary approaches to the implementation of ecological design. The study identifies fabrics and materials most aligned with the principles of eco-design, which are increasingly favored by contemporary fashion designers. Ultimately, the article outlines the issue of eco-fashion as a promising direction for enhancing personal well-being, preventing ecological crises, and improving management practices within the light industry sector.